Development Assistance for a New Era? The Reconfiguration of CSO Agency in Swedish Development Cooperation - Loustalot,Miguel (2025)
This thesis examines how Sweden’s new development policy, Development for a New Era, reconfigures the agency of its civil society organizations (CSOs). The policy marks a major shiftin Sweden’s foreign aid landscape, moving from a human rights– and needs-based approach to one driven by strategic, trade, and migration interests. Drawing on a qualitative analysis of interviews with CSO staff and media publications, the study finds that the new policy has significantly constrained CSO agency—not only through the changes formally set out in policy documents, but also through factors linked to its implementation and the deterioration of CSO–government relations. The research concludes that CSO agency has not been entirely suppressed but rather displaced. Excluded from their traditional role as policy partners, CSOs have been pushed into the position of external watchdogs, creating new spaces for resistance through public dissent and mediaadvocacy. Ultimately, this transformation in Swedish aid policy threatens the long-term prospectsfor a pluralistic and autonomous civil society within Sweden’s development cooperation sector.
Keywords: Swedish aid policy; CSO agency; development reform; power reconfiguration; shrinking civil space